Multiple Eruptive Epithelioid Hemangiomas: A Subset of Cutaneous Cellular Epithelioid Hemangioma With Expression of FOS-B. (January 2019) - Llamas-Velasco, Mar; Kempf, Werner; Cota, Carlo; Fernández-Figueras, Maria Teresa; Lee, Joyce; Ferrara, Gerardo; Sander, Christian; Shapiro, Philip E.; Requena, Luis; Kutzner, Heinz
Abstract : There is a wide clinicopathologic spectrum of vascular proliferations characterized by the presence of epithelioid endothelial cells, comprising epithelioid hemangioma (EH)—pseudomyogenic (epithelioid sarcoma-like) hemangioendothelioma (PM-HAE), epithelioid hemangioendothelioma, and epithelioid angiosarcoma. Immunohistochemical FOS-B expression as well as FOS-B rearrangement (fluorescent in situ hybridization [FISH]) have recently been described as diagnostically relevant underpinnings of EH (restricted to osseous lesions) and PM-HAE. The aim of this study was to clinicopathologically characterize and to elucidate FOS-B expression in patients with eruptive lesions of the cellular variant of cutaneous EH. All cases of cutaneous cellular EH (n=16) showed strong diffuse immunohistochemical expression of FOS-B, in conjunction with positivity for ERG and nestin. Expression of MYC, CAMTA-1, AE1/3, and MNF116 was negative in all cases. FISH investigations did not show any sign of rearrangements for CAMTA-1 or MYC amplification. Negative-control cases included 15 lobular hemangiomas, 5 epithelioid angiosarcomas, and 5 nodular Kaposi sarcomas, all of which were negative for FOS-B. Positive-control cases included 15 angiolymphoid hyperplasia with eosinophilia cases, all of them being positive. In contrast with what has been published so far, cutaneous variants of cellular EH exhibit positive immunostaining for FOS-B. Remarkably, FOS-B expression is not restricted to the intraosseous subset of EH. For differential diagnosis of epithelioid vascular tumors, we therefore suggest a helpful panel of antibodies including CAMTA-1, TFE-3, FOS-B, and AE1/AE3. We point out the telltale immunophenotypes: angiolymphoid hyperplasia with eosinophilia and EH (FOS-B + /others negative), PM-HAE (FOS-B + /AE1/AE3 + /others negative), epithelioid hemangioendothelioma (CAMTA-1 + or TFE-3 + /others negative). Remarkably, MYC is not expressed in these tumors, neither is there an MYC amplification by FISH. We suggest the term multiple eruptive EHs for this subset of cutaneous vascular tumors. Abstract : Supplemental Digital Content is available in the text.